2021
DOI: 10.3390/antiox10030374
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Inflammaging Ability of Prune (Prunus Spinosa L.) Extract Result in Improved Wound Healing Efficacy

Abstract: Prunus spinosa L. fruit (PSF) ethanol extract, showing a peculiar content of biologically active molecules (polyphenols), was investigated for its wound healing capacity, a typical feature that declines during aging and is negatively affected by the persistence of inflammation and oxidative stress. To this aim, first, PSF anti-inflammatory properties were tested on young and senescent LPS-treated human umbilical vein endothelial cells (HUVECs). As a result, PSF treatment increased miR-146a and decreased IRAK-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…In addition, extracts of other Prunus spp. such as Prunus spinos showed antioxidant and anti-inflammatory properties [453,454]. Zhengtian Capsule is a Chinese patent medicine that consists of a mixture of 15 herbs including Prunus persica [455].…”
Section: Prunus Sppmentioning
confidence: 99%
“…In addition, extracts of other Prunus spp. such as Prunus spinos showed antioxidant and anti-inflammatory properties [453,454]. Zhengtian Capsule is a Chinese patent medicine that consists of a mixture of 15 herbs including Prunus persica [455].…”
Section: Prunus Sppmentioning
confidence: 99%
“…Further, the Prunus extract (400 µg/mL) increased the life and health span in C. elegans. Overall, the study indicated that P. spinosa fruit extract might enhance wound healing capacity in senescent conditions, thereby improving the quality of life in aging populations [126].…”
Section: Blueberrymentioning
confidence: 82%
“…In past studies, different scientists [4,9,10,89,[95][96][97] have demonstrated a significant antioxidant activity of blackthorn extracts by 2,2-diphenyl-1-picrylhydrazyl test, knowing the fact that fruits with a high capacity of radical scavenging are associated with low occurrences of degenerative diseases (inflammation and arthritis) [98]. Blackthorn fruit ethanolic extract was investigated for its wound-healing capacity by Coppari et al (2021) [99]. The human umbilical vein endothelial cells were mechanically scratched within T25 tissue culture flasks and then subjected to evaluation using a phase contrast microscope.…”
Section: Anti-inflammatory Effectmentioning
confidence: 99%